Analysis of the Spatio-Temporal Evolution Characteristics and Influencing Factors of Habitat Quality in Hubei Province over the Past Three Decades - Jie Miao; Huiqiong Xia; Fu Li; Jialin Yang (ISPRS International Journal of Geo-Information)
A region’s ability to maintain biodiversity and the health of its ecosystems depends heavily on the quality of its habitat. The Integrated Valuation of Ecosystem Services and Trade-offs (InVEST) model was utilized in this investigation, in conjunction with the Geographic Detector (Geodetector) model and Geographic Information System (GIS) spatial analysis techniques, to systematically analyze the spatio-temporal evolution characteristics and underlying driving mechanisms of habitat quality in Hubei Province from 1990 to 2020. The findings indicate that over the period of thirty years, there has been a significant decline in the habitat quality index in the eastern part of Hubei Province, while the western region has maintained a relatively high level. Additionally, habitat quality in several areas declined continuously over the 30-year period. The results of spatial autocorrelation showed that the habitat quality in the western part of Hubei Province from 1990 to 2020 was mainly characterized by High-High Clusters, while the eastern parts of the province mostly showed Low-Low Clusters. According to the findings of the Geographic Detector research, the degree of influence of each driver on habitat quality varies significantly over time, with the Construction Land Index being the main factor influencing habitat quality in Hubei Province. Moreover, the interaction between factors exerted a stronger influence on habitat quality compared to individual factors. This research result has deepened the understanding of the changing law of habitat quality in Hubei Province and has laid a solid foundation for scientists to develop targeted ecological protection strategies in the future. The results of the study have provided a reference for habitat quality assessment in other regions, especially in the process of analyzing the spatial and temporal evolution patterns of habitat quality in different regions and under different ecosystem types, which has provided more reference for ecological protection.